2019
DOI: 10.1590/s0102-8650201900207
|View full text |Cite
|
Sign up to set email alerts
|

Gum arabic and red propolis protecteting colorectal preneoplastic lesions in a rat model of azoxymethane

Abstract: Purpose To evaluate red propolis, gum arabic and L-lysine activity on colorectal preneoplastic lesions induced by azoxymethane (AOM). Methods The study featured 4 control groups (I-IV) and 4 experimental groups (V-VIII), totaling 48 rats. Once a week for 2 weeks, animals on control groups received saline, while animals in experimental groups received azoxymethane (15 mg/kg i.p.). The follow up along 16 weeks included daily oral gavage to administer water (I and V), L-ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…However, various doses of propolis combined with 5FU significantly reduced the number of ACFs compared to the treatment with 5FU alone, which indicated its synergistic effect with 5FU in mouse model Balb/c. The protective influence of propolis on the process of colon carcinogenesis in animal models was also observed by other authors [ 66 , 67 , 68 , 69 , 70 ]. A number of in vitro and in vivo studies confirmed the efficacy of the anti-cancer effects of propolis and encourage researchers to conduct clinical trials.…”
Section: Bee Products—anti-colon Cancer Potentialsupporting
confidence: 80%
“…However, various doses of propolis combined with 5FU significantly reduced the number of ACFs compared to the treatment with 5FU alone, which indicated its synergistic effect with 5FU in mouse model Balb/c. The protective influence of propolis on the process of colon carcinogenesis in animal models was also observed by other authors [ 66 , 67 , 68 , 69 , 70 ]. A number of in vitro and in vivo studies confirmed the efficacy of the anti-cancer effects of propolis and encourage researchers to conduct clinical trials.…”
Section: Bee Products—anti-colon Cancer Potentialsupporting
confidence: 80%
“…Reduces number of aberrant crypt foci in distal colon and TBARS levels in peripheral blood. [171] DMBA-induced oral squamous cell carcinomas in rats.…”
Section: Propolis Administeredmentioning
confidence: 99%
“…After 16 weeks, treatment with propolis (100 mg/mL) reduced the number of aberrant crypt foci in the distal colon. In addition, propolis reduced the TBARS (thiobarbituric acid reactive substances) levels in peripheral blood, suggesting a protective activity of Brazilian propolis in the colon, possibly associated with its antioxidant properties [ 171 ]. Similarly, the effect of oral administration of Brazilian red propolis (10, 50 and 100 mg/kg) for 26 weeks on oral squamous cell carcinomas (OSCC) in rats induced by 9,10-dimethyl-1,2-benzanthracene (DMBA) was investigated.…”
Section: Biomedical Properties Of Propolis On Diabetes Obesity Amentioning
confidence: 99%
“…All three yielded significant IC 50 values and performed better than the vitamin C standard (12). Also, our team tested the ability of red propolis treatment for 16 weeks to reduce oxidative stress based on TBARS quantification in peripheral blood of rats with azoxymethane-induced colon cancer (23). The development of the present experimental study was motivated by the results of in vitro and in vivo studies of the pathophysiology of CP-induced hemorrhagic cystitis and its association with oxidative stress (19).…”
Section: Discussionmentioning
confidence: 99%